THE ART OF HYPNOSIS: HOW TO REDUCE THE AFFECTIVE DIMENSION OF PAIN. A LITERATURE REVIEW - Corina DONDAȘ; Magdalena IORGA; Ion DAFINOIU (Studia Universitatis Babeș-Bolyai. Philosophia, 2017)
Interest in hypnotic treatment for pain conditions seems to be on the rise. Recent evidence shows that hypnotic analgesia interventions result in substantial cost savings following medical procedures. Experimental studies suggest that hypnosis can differentially modulate the sensory or affective dimension of pain, depending on the nature of the suggestions. However, there have been few systematic approaches to quantifying this effect across literature and less attention has been given to the specific procedures and suggestions used in hypnotic treatment in research. The present paper evaluates the magnitude of the effect of hypnosis on the affective component of pain. A scientific background presents the usefulness of a hypnotic approach that uses emotion-specific wording that would elicit prior positive experience to intervene at both the sensory and affective dimensions of pain. Such an approach would enable patients who cannot effectively dissociate from the sensation of pain to diminish their affective response. The paper concludes with a discussion of the implications of the findings for future hypnosis research and for the clinical applications of hypnotic analgesia.